Türkiye’de Sıcaklık Değişimleri ve Trendlerin Belirlenmesi - Halil Oruç; Tuğba Çelebioğlu; Mete Tayanç (Uludağ University Journal of The Faculty of Engineering, 2021)
A comprehensive study has been carried out for Turkey to investigate temperature variabilities and trends in a 50-year period of 1969-2018. Daily temperature data belonging to 174 meteorological stations which was collected from Turkish Meteorological State Service was used in this research. Temporal and spatial variability of temperature have been studied by linear regression, 3-yr moving average and non-parametric Mann-Kendall test. Yearly and seasonally average temperature of each region has been formed from analysis of daily average temperature for this time period. Temperature increase in this recent half century time period is found to be in the Eastern Anatolia Region with a value of 1.74°C/50 years. The regions with the highest seasonal temperature increases are estimated to be the Aegean Region (1.61°C) in autumn, Eastern Anatolia Region (2.37°C) in winter, Eastern Anatolia Region (1.84°C) in spring and Marmara Region in summer (2.79°C). Moreover, yearly temperature trends showed increasing trends at 99% confidence interval in most stations. Increasing trends at 99% confidence interval have been confirmed in most regions from analyzing seasonally and yearly temperature trends.